The View from Jacob Street: Reframing Urban Renewal in Postwar Halifax - Loo, Tina (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2019)
By focusing on the period immediately following planner Gordon Stephenson’s redevelopment study of Halifax in 1957 and before the start of the Africville relocation in 1964, we gain a different appreciation of the scale of displacement, the interplay of race and class in shaping people’s vulnerability to urban renewal, and the power of the municipal state. Understanding these early redevelopment efforts also provides us with a different perspective on Africville. The city’s actions there were shaped by shifting attitudes towards racism and an attempt, albeit inadequate, to rectify it by focusing on one of its most visible manifestations – segregation.